2016
DOI: 10.3989/scimar.04297.06b
|View full text |Cite
|
Sign up to set email alerts
|

Artificial upwelling using offshore wind energy for mariculture applications

Abstract: Summary: Offshore wind is proposed as an energy source to upwell nutrient-rich deep water to the ocean photic layers. A spar-buoy wind turbine with a rigid tube about 300 m long is proposed as a pipe to drive deep water up to the surface. The minimum energy required to uplift the water is the potential energy difference between surface waters inside and outside the pipe, which depends on the background density profile. The corresponding surface jump or hydraulic head, h, calculated for several analytical and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The renewable energy should be preferable to AU to assure feasibility and sustainability. Research on renewable energy for the task of raising DOW levels has focused on using offshore wind for mariculture applications [55], using wave energy for phytoplankton bloom stimulation [19], and using perpetual salt fountain to increase primary production [56,57]. A distributed generation (DG) power supply system that consists of DG units of a wind turbine, a wave energy converter (WEC) array, a PV array, and a diesel generator was investigated by our group and utilized in air-lift AU [17].…”
Section: Discussionmentioning
confidence: 99%
“…The renewable energy should be preferable to AU to assure feasibility and sustainability. Research on renewable energy for the task of raising DOW levels has focused on using offshore wind for mariculture applications [55], using wave energy for phytoplankton bloom stimulation [19], and using perpetual salt fountain to increase primary production [56,57]. A distributed generation (DG) power supply system that consists of DG units of a wind turbine, a wave energy converter (WEC) array, a PV array, and a diesel generator was investigated by our group and utilized in air-lift AU [17].…”
Section: Discussionmentioning
confidence: 99%
“…Offshore wind arrays can offer protection to fish stocks and should therefore co-locate with fishing activities or around the fish farm cages (Zanuttigh et al, 2016). The offshore wind turbine could also be designed to provide the energy to create an artificial upwelling of the nutrient-laden waters from the deep to increase the surface fish production and thus bring more benefit to the fishing activities within the areas (Viúdez et al, 2016). By benefitting from ecological, technical, and socioeconomic evidences, the development of OWFs under MU is a feasible direction to maximize the synergies, optimize efficient use of marine space, and promote the use of resource diversity (Schupp et al, 2019).…”
Section: Multi-use Between Owfs and Fisheriesmentioning
confidence: 99%
“…The results showed that enhancing carbon sink and nutrient removal through AU is feasible. However, the promotion of AU also faces challenges, including its low energy efficiency and high installation costs (Fan et al, 2013;Viudez et al, 2016;Qiang et al, 2018). These challenges need to be considered in successful implementation of AU technology and achievement of better results in Shandong Province and other coastal areas.…”
Section: Improving Key Factors That Influence Carbon Sinks and Nutrie...mentioning
confidence: 99%